Tekstowy wszechświat Leśmiana - Winiecka, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article discusses Żaneta Nalewajk’s book Leśmian międzynarodowy. It presents the Leśmian’s work read in the context of the work of Poe, Ukrainian folklore, Ruthenian perennials as well as French and Russian symbolism. The author takes note of the numerous qualities of the dissertation. She is pointing at several advantages of this work; its analytical reliability and the methodological consequence. The author shows also on the important position of the publication in the research on the poetry of Bolesław Leśmian. She notices one essential lack which is an omission of important continuations of Leśmian’s poetics in Polish modern poetry.